Uniform magnetic fields in density-functional theory - Tellgren, Erik I.; Laestadius, Andre; Helgaker, Trygve; Kvaal, Simen; Teale, Andrew M. (American Institute of Physics, 2018)
We construct a density-functional formalism adapted to uniform external magnetic fields that is intermediate between conventional Density Functional Theory and Current-Density Functional Theory (CDFT). In the intermediate theory, which we term LDFT, the basic variables are the den- sity, the canonical momentum, and the paramagnetic contribution to the magnetic moment. Both a constrained-search formulation and a convex formulation in terms of Legendre–Fenchel transfor- mations are constructed. Many theoretical issues in CDFT find simplified analogues in LDFT. We prove results concerning N-representability, Hohenberg–Kohn-like mappings, existence of minimiz- ers in the constrained-search expression, and a restricted analogue to gauge invariance. The issue of additivity of the energy over non-interacting subsystems, which is qualitatively different in LDFT and CDFT, is also discussed.